2009
DOI: 10.1099/ijs.0.005215-0
|View full text |Cite
|
Sign up to set email alerts
|

Algoriphagus aquatilis sp. nov., isolated from a freshwater lake

Abstract: A Gram-negative, non-spore-forming, non-motile bacterium, strain A8-7 T , was isolated from fresh water of a slightly alkaline lake, Longhu Lake, in Daqing, north-east China, and its taxonomic position was studied by using a polyphasic approach. Strain A8-7 T was aerobic, heterotrophic and positive for catalase and oxidase. It grew at 20-37 6C (optimum 30 6C) and pH 5.5-10.5 (optimum pH 7.5) and in the presence of 0-3 % (w/v) NaCl. It formed pink-pigmented, smooth and circular colonies, 1-2 mm in diameter, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…The major (.5 %) fatty acids were iso-C 15 : 0, summed feature 3 (C 16 : 1 v7c/iso-C 15 : 0 2-OH), summed feature 9 (iso-C 17 : 1 v9c/10-methyl C 16 : 0 ) and minor amount of iso-C 16 : 0 , iso-C 17 : 0 3-OH, C 16 : 1 v5c, anteiso-C 15 : 0 , summed feature 4 (C 17 : 1 iso I/C 17 : 1 ), iso-C 15 : 0 3-OH, C 17 : 1 v6c, C 16 : 0 3-OH, iso-C 16 : 1 H, C 15 : 1 v6c, and iso-C 17 : 0 were also present. Overall, the results obtained in this study are in agreement with previously published data for ten species of the genus Algoriphagus (Liu et al, 2009;Nedashkovskaya et al, 2004Nedashkovskaya et al, , 2007Park et al, 2010;Van Trappen et al, 2004;Yoon et al, 2005aYoon et al, , b, 2006, but differed from those of the type species of the genus, A. ratkowskyi DSM 22686…”
Section: Colonies Of Strain Cau 1002supporting
confidence: 92%
See 1 more Smart Citation
“…The major (.5 %) fatty acids were iso-C 15 : 0, summed feature 3 (C 16 : 1 v7c/iso-C 15 : 0 2-OH), summed feature 9 (iso-C 17 : 1 v9c/10-methyl C 16 : 0 ) and minor amount of iso-C 16 : 0 , iso-C 17 : 0 3-OH, C 16 : 1 v5c, anteiso-C 15 : 0 , summed feature 4 (C 17 : 1 iso I/C 17 : 1 ), iso-C 15 : 0 3-OH, C 17 : 1 v6c, C 16 : 0 3-OH, iso-C 16 : 1 H, C 15 : 1 v6c, and iso-C 17 : 0 were also present. Overall, the results obtained in this study are in agreement with previously published data for ten species of the genus Algoriphagus (Liu et al, 2009;Nedashkovskaya et al, 2004Nedashkovskaya et al, , 2007Park et al, 2010;Van Trappen et al, 2004;Yoon et al, 2005aYoon et al, , b, 2006, but differed from those of the type species of the genus, A. ratkowskyi DSM 22686…”
Section: Colonies Of Strain Cau 1002supporting
confidence: 92%
“…At the time of writing, this genus comprised 19 species with validly published names (http://www.bacterio.cict.fr/). Recently, members of the genus Algoriphagus have been isolated from various environmental habitats such as freshwater (Liu et al, 2009;Rau et al, 2012), oilcontaminated soil (Young et al, 2009), a tidal flat sediment (Park et al, 2010) and seawater (Oh et al, 2012). Members of this genus are Gram-negative, rod-shaped, non-motile, non-sporulating, and possess menaquinone-7 (MK-7) as the major respiratory quinone and iso-C 15 : 0 as the predominant cellular fatty acid (Yoon et al, 2006).…”
mentioning
confidence: 99%
“…All are negative for fermentation of glucose and gliding motility. Data for reference species are from Ahmed et al (2007), Bowman et al (2003), Liu et al (2009, Tiago et al (2006), , Yi & Chun (2004) and Yoon et al (2005aYoon et al ( , b, 2006 …”
Section: Description Of Algoriphagus Olei Sp Novmentioning
confidence: 99%
“…Comparative 16S rRNA gene sequence analysis indicated that strain 12C11 T formed a clade with the genus Algoriphagus, which belongs to the family Cyclobacteriaceae. At the time of writing, the genus Algoriphagus comprised 23 recognized species: Algoriphagus ratkowskyi (Bowman et al, 2003), A. ornithinivorans (Yi & Chun, 2004), A. antarcticus , A. halophilus , A. marincola (Yoon et al, 2004), A. aquimarinus , A. mannitolivorans (Nedashkovskaya et al, 2007;Yi & Chun, 2004), A. chordae , A. winogradskyi , A. locisalis (Yoon et al, 2005a), A. yeomjeoni (Yoon et al, 2005b), A. terrigena (Yoon et al, 2006), A. boritolerans (Ahmed et al, 2007), A. alkaliphilus (Nedashkovskaya et al, 2007), A. vanfongensis (Nedashkovskaya et al, 2007), A. hitonicola (Copa-Patiño et al, 2008), A. aquatilis (Liu et al, 2009) (Li et al, 2011), A. jejuensis , A. namhaensis (Oh et al, 2012), A. aquaeductus (Rau et al, 2012) and A. machipongonensis (Alegado et al, 2013). The genera Hongiella and Chimaereicella were reclassified within the genus Algoriphagus based on phylogenetic evidence and chemotaxonomic and phenotypic data (Nedashkovskaya et al, 2007).…”
mentioning
confidence: 99%